(untitled) (Jurnal Proaksi, 2025)
Main Purpose - This study aims to provide an in-depth understanding of research in the field of environmental reporting. Method - This article presents a bibliometric analysis of the environmental reporting literature using the Scopus database. Main Findings – Research on environmental reporting shows a strong relationship between certain topics and certain author journals. Some journals and author specialize or are interested in specific aspects of environmental reporting research, such as sustainability, corporate social responsibility, environmental disclosure, and legitimacy theory. Theory and Practical Implications - The theoretical implications of this study provide an understanding of research trends and the potential to expand collaboration in regions or countries that have not been heavily involved in the field of environmental reporting. The practical implication is the importance of academics to fill the research gap in developing countries. Novelty – The analysis was conducted to see the development trend of environmental reporting research and to conduct a comprehensive mapping of the development of environmental reporting.